Book Review: Experimentelle Archäologie, Jahrbuch 2022 - Stefanie Ulrich (EXARC Journal)
The periodical is published by Gunter Schöbel and the European Association for the Advancement of Archaeology by Experiment e. V. (Europäische Vereinigung zur Förderung der Experimentellen Archäologie) in collaboration with the Pfahlbaummuseum Unterhuldingen.